Voice from the Beehive: structuring and recording responsible innovation for novel technologies - C. Ten Holter; M. Jirotka (Journal of Responsible Innovation)
Societal trust in research and innovation is predicated on factors such as governance, safety, and responsible development. These are often thought of as regulatory matters, but regulation may be ill-adapted for many novel technologies. Anticipatory governance, potentially in the form of responsible innovation (RI), can help to provide this adaptivity and granularity. However, RI remains new to many fields, and can be difficult to apply. This paper analyses the literature to identify challenges for RI and lessons from other domain frameworks, synthesising this with empirical evidence to develop a Framework. The Beehive Framework is a straightforward to use, translatable scaffold, with accompanying guidance for mapping and recording RI within projects of various scales and types. Its iterative process model approach to RI contains elements of project management methodology, and captures information gathered during the processes of RI. It records these processes for further iteration, and comparison between projects.